Las tierras incógnitas de la administración jesuita: toma de decisiones, gremios consultivos y evolución de normas - Fechner, Fabián (2014)
In spite of the well-known importance of written norms and administrative structures in the Society of Jesus, there are only a few specialized studies of these subjects. A very general concept of a monolithic and centralized religious order is prevalent. But when administrative practices and internal communication are analyzed thoroughly, it becomes clear that Jesuit structures were based on consultative guilds which took part in decision-making processes. Among the least investigated administrative topics, the freedom of action of provincial congregations is most surprising.